Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/jnr.23929
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte‐produced leukemia inhibitory factor expands the neural stem/progenitor pool following perinatal hypoxia–ischemia

Abstract: Brain injuries, such as cerebral hypoxia-ischemia (H–I), induce a regenerative response from the neural stem/progenitors (NSPs) of the subventricular zone (SVZ); however, the mechanisms that regulate this expansion have not yet been fully elucidated. The Notch-DSL signaling pathway is considered essential for the maintenance of neural stem cells, but it is not known if it is necessary for the expansion of the NSPs subsequent to perinatal H–I injury. Therefore, the aim of this study was to investigate whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…LIF-1 is well known to activate the Jak/Stat pathway, which has been shown to reduce symmetric division of myogenic precursors, which would possibly signify return to quiescence, and to promote fusion into myotubes (at the other end of myogenic lineage) 42 . But LIF-1 also activates the MAPK signaling, which can induce the Notch activating ligands Delta and Jagged, promoting myogenic proliferation 43 , 44 .…”
Section: Discussionmentioning
confidence: 99%
“…LIF-1 is well known to activate the Jak/Stat pathway, which has been shown to reduce symmetric division of myogenic precursors, which would possibly signify return to quiescence, and to promote fusion into myotubes (at the other end of myogenic lineage) 42 . But LIF-1 also activates the MAPK signaling, which can induce the Notch activating ligands Delta and Jagged, promoting myogenic proliferation 43 , 44 .…”
Section: Discussionmentioning
confidence: 99%
“…NSC populations upregulate LIF mRNA following stimulation with interferon γ, which is produced by T lymphocytes and natural killer cells after stroke. This secretion of LIF promotes brain repair by acting on neural cells and by triggering proliferation of other NSCs (Felling, Covey, Wolujewicz, Batish, & Levison, 2016; Laterza et al, 2013; Yilmaz, Arumugam, Stokes, & Granger, 2006). Neurons also increase expression of LIF in response to injury.…”
Section: Treatment Of Neurodegenerative Diseasementioning
confidence: 99%
“…In their 2006 paper, Felling et al (50) provided evidence implicating Notch signaling in the expansion of the neural progenitor (NP) pool. More recently, Felling et al (51) used an in vitro model for H-I, hypoglycemia, and hypoxia (H-H), and showed that H-H itself is not sufficient to induce Notch-1, but that H-H induces astrocytes to produce leukemia inhibitory factor, which in turn increases Notch1 expression in the neural stem/ progenitors (NSPs). There is a controversy as to whether neonatal H-I increases the proportion of bona fide neural stem cells vs. progenitors.…”
Section: Hypoxic-ischemic Encephalopathymentioning
confidence: 99%
“…Notch receptors are transmembrane proteins that are activated by membrane bound Delta and Jagged ligands and they are expressed by the stem cells and progenitors in the SVZ (94). Studies by Felling et al (50,51) showed that H-I increases the expression of Notch1 as well as one of its ligands, Delta-like 1, that results in increased expression of the downstream effectors, Hes1 and Hes5, within the NSPs of the SVZ. They further showed that pharmacologically decreasing Notch1 activity during the acute recovery period in vivo abrogated the increase in NSPs seen after neonatal H-I.…”
Section: Signaling Molecules That Are Produced After Peri-natal Brainmentioning
confidence: 99%
See 1 more Smart Citation